Urban Climate Governance, Adaptation, and Human Rights: The Case of the ‘Resilient Municipalities of São Paulo’ Project (Municípios Paulistas Resilientes) - Seleguim, Fabiana Barbi; Lemos, Patricia Faga Iglecias (My University, 2025)
This article analyzes aspects of urban climate governance with a focus on adaptation and the promotion and protection of human rights in Brazilian cities. It argues that the threat to human rights in cities does not arise from climate change itself, but from the lack of adequate political actions, or the failure of these actions, related to mitigating climate change, enhancing adaptive capacity and building resilience among vulnerable social groups. The methodology includes a literature review and a case analysis of the project "Resilient Municipalities of São Paulo". The article concludes that climate governance with multi-level, multi-actor, multi-sectoral, multi-dimensional, and multi-knowledge aspects is essential to ensure the protection of human rights and adapt populations to the challenges of the climate emergency.
Keywords: Comunicação Social; UNIDADE::SECRETARIA DE INTEGRIDADE PÚBLICA (SIP); adaptation; climate emergency; urban areas; climate justice; resilience; ASSUNTO::Comunicação Social